Factors Related to Completeness of Basic Immunization During the Covid-19 Pandemic at PMB I.S Kebon Jeruk West Jakarta 2021 - Agustina, Indah Fitri; Saudur Romian Rumapea, Risnauli; Partono, Partono (JOURNAL EDUCATIONAL OF NURSING(JEN), 2021)
Diseases caused by infections are still a health problem in developing countries, including Indonesia. According to the World Health Organization (WHO) in 2018, an estimated 19.9 million babies worldwide were not reached by routine immunization services. Around 60% of these children living in 10 countries including Indonesia are not immunized. One of the international commitments to improve the health status of children is the UCI (Universal Child Immunization) program, which is a state of achieving complete basic immunization for infants. Immunization. This research is a quantitative study with a cross-sectional design, using primary data with a sample of 108 mothers and infants and data analysis using chi-square. There was a significant relationship between nutritional status (p value = 0.040), baby's medical history (p value = 0.040), mother's knowledge (p value = 0.001), distance from home (p value = 0.044), health insurance (p value = 0.040) In conclusion, there is a significant relationship with all the variables studied, suggestions for mothers who have babies should immunize their children on time, considering that immunization is very important to equip their children with health in the future